Planning for Minimal Soil Loss from Crop Fields in Kandhamal District of Orissa - Panigrahi, Dwitikrishna; Acharya, Milu; Senapati, P C (Journal of Agricultural Engineering, 2008)
The climatic data of Kandhamal district of Orissa for 17 years were analyzed and correlated with crop coefficient to find out suitable cropping periods and sequences. The soil losses per hectare of crop cultivation for the forty possible crop sequences were calculated. The food requirement of the district for nutritional sufficiency as per the recommended dietary allowance for a projected population during 2011 was estimated. A mathematical model for optimal allocation of the cultivable areas to the crop sequences with the objective of minimization of soil loss from crop fields was formulated and solved using linear programming technique. The model suggested to take up food crops in an area of 1,30,777 ha with a cropping intensity of 161 per cent (100 per cent in kharif, 58 per cent in pre rabi and 3 per cent in rabi) and to take up perennial grass cover in 3,223 ha resulting in loss of soil of 9489.67 thousand tons per year against the present level of 12626.95 thousand tonnes per year.